Green synthesis of ZnO-Silica composite from bamboo husk and its application for the photodegradation of direct blue 86 dye - Nazwa Putri Adira; Ferdiansyah; Inggrit Desti Utami; Poedji Loekitowati Hariani (Institute for Advanced Social, Science, and Sustainable Future, 2025)
Background: The textile industry in Indonesia is rapidly growing, contributing to increasing synthetic dye waste, particularly Direct Blue 86 (DB-86), which is toxic and resistant to natural degradation. This study aims to develop an eco-friendly composite of ZnO-Silica through green synthesis using bamboo peel and Ketapang leaf extract for the photodegradation of DB-86. Methods: This study employs a literature review method to collect, analyze, and synthesize scientific data on the green synthesis of ZnO-silica composites from bamboo peel and their application in the photodegradation of Direct Blue 86 dye. Data were obtained from recent scholarly sources and analyzed through comparative synthesis and interpretation to evaluate the efficiency and potential of the materials in wastewater treatment. Findings: The findings of this study reveal that ZnO-silica composites synthesized via green synthesis using Ketapang leaf extract and bamboo peel-derived silica demonstrated high photocatalytic efficiency in degrading Direct Blue 86. Using the sol-gel method, the composite achieved a degradation efficiency of up to 99.10%. The optimal conditions included a catalyst dosage of 10 mg, dye concentration of 10 mg/L, and extended irradiation time. Compared to other catalysts like TiO₂ and MgO, the ZnO-silica composite showed competitive performance with lower required dosage and comparable degradation rates. Conclusion: The study concludes that bamboo peel, with its high silica content (98.31%), and ZnO derived from Ketapang leaves are effective and eco-friendly materials for the photodegradation of Direct Blue 86 dye, especially when synthesized using the sol-gel method with up to 99.10% efficiency. Novelty/Originality of this article: The novelty of this article lies in the innovative use of bamboo peel-derived silica and Ketapang leaf extract in a green synthesis approach to produce ZnO-silica composites for degrading Direct Blue 86 dye.